A study of climate change impacts on hydrologic regime of the Vogršček accumulation (SW Slovenia) - Trček, Branka (Geologija, 2005)
Climate change impacts on hydrologic regime of the Vogršček accumulation (Vipava valley) were studied for a decade period 1995-2004. During this time water capture from the accumulation has been increased. Although a pumping did not influence the accumulation level a lot, it oscillated much different during single halves of the decade. The results indicated that this could result from a decrease of effective precipitation amounts, which recharge the accumulation, from changes of their distribution, as well as from an increased frequency of extreme dry periods and extreme precipitation events during the second decade half.